To history of the Russian translation reception of poetry of Robert Buchanan - Zhatkin, Dmitry; Kruglova, Tatiana; Milotaeva, Olga (Revista Inclusiones, 2019)
Objectives: The article is devoted to judgment of literary originality of interpretations of poems "Liz" and "Nell" from Robert Buchanan's cycle "London Poems" created at a boundary of 1870-1880s by the Russian translator D.E. Minh (1818–1885). Methods: R. Buchanan’s poems "Liz" and "Nell" and their first Russian translations "London idyll", the "Death penalty in London" by D.E. Minh was of some interest for the analysis. Comparative and historical and comparative and typological methods and also devices of complex analysis were used in the work. Findings: The detailed analysis of ideological and thematic content of translations in comparison to the originals is carried out. The specifics of D.E. Minh’s translation principles are established. Special attention is paid to the changes of formal and substantial character introduced by D.E. Minh, in particular, to the reduction of number of repetitions of separate words that give the nature of lamentation, mourning of the hard destiny to women’s confessions. Novelty: The translations from R. Buchanan’s cycle "London poems" are not so much directed to exact reconstruction of English originals. They reveal features of D.E. Minh’s inner world where some motives of sympathy to the disadvantaged, search of justice in society and in the human relations amplified. This circumstance in general is unusual to D.E. Minh’s creative works who was traditionally seeking for scrupulous reconstruction of literary details of originals.